2019
DOI: 10.1155/2019/3756750
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for Prevention and Relief of Cardiovascular Disease: Prognoses, Mechanisms, and Approaches

Abstract: This review is aimed at summarizing the new findings about the multiple benefits of exercise on cardiovascular disease (CVD). We pay attention to the prevalence and risk factors of CVD and mechanisms and recommendations of physical activity. Physical activity can improve insulin sensitivity, alleviate plasma dyslipidemia, normalize elevated blood pressure, decrease blood viscosity, promote endothelial nitric oxide production, and improve leptin sensitivity to protect the heart and vessels. Besides, the protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 127 publications
(130 reference statements)
1
83
0
2
Order By: Relevance
“…In contrast to antioxidant supplements, chronic exercise training has been characterized as a non-pharmacological tool to prevent or treat many CVDs since it elicits cardio-protective effects via multiple mechanisms. Specifically, there has been reported that regular exercise is capable of improving insulin sensitivity and lipid metabolism, regulating autonomic function [55], reducing blood pressure and blood viscosity, enhancing endothelial nitric oxide production as well as improving leptin sensitivity [56]. Moreover, exercise increases the mitochondrial biogenesis, fatty acid oxidation and the dilation of blood vessels, that results in improved myocardial perfusion and lower inflammation, reducing as such the risk for atherosclerosis [57].…”
Section: Antioxidants Oxidative Stress and Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to antioxidant supplements, chronic exercise training has been characterized as a non-pharmacological tool to prevent or treat many CVDs since it elicits cardio-protective effects via multiple mechanisms. Specifically, there has been reported that regular exercise is capable of improving insulin sensitivity and lipid metabolism, regulating autonomic function [55], reducing blood pressure and blood viscosity, enhancing endothelial nitric oxide production as well as improving leptin sensitivity [56]. Moreover, exercise increases the mitochondrial biogenesis, fatty acid oxidation and the dilation of blood vessels, that results in improved myocardial perfusion and lower inflammation, reducing as such the risk for atherosclerosis [57].…”
Section: Antioxidants Oxidative Stress and Cardiovascular Diseasementioning
confidence: 99%
“…Numerous epidemiological studies have convincingly demonstrated the beneficial effect of physical exercise on CVD outcomes, and thus, it has been considered as a valuable therapeutic approach for CVDs [56,[66][67][68][69]. The favorable effect of regular exercise on CVDs progress is primarily attributed on the exercise-mediated enhancement of the antioxidant capacity and reduction of oxidative stress levels that subsequently results in redox balance preservation and cellular homeostasis [63,64].…”
Section: Exercise Cardiovascular Disease and Oxidative Stressmentioning
confidence: 99%
“…Most studies indicate that regular exercise training leads to beneficial effects on cardiovascular indices such as blood lipids, insulin resistance and leptin concentration [12,13]; however, the duration and intensity of exercises should be enough. Sheikholeslami-Vatani, et al reported that concurrent training is the best method to enhance health level, improve physical fitness and decrease cardiovascular risk factors [14].…”
Section: Participantsmentioning
confidence: 99%
“…Physioprophylaxis allows, to a large extent, to avoid or inhibit the development of functional problems or diseases. It also helps to prevent civilization diseases, the aging process and disability by doing professional and daily tasks ergonomically as well as behaviors that strengthen health protective factors aimed at preventing health threats [1][2][3][4][5]. It is a new and effective alternative in the health care system.…”
Section: Introductionmentioning
confidence: 99%